Game features of cognitive training - Craven, Michael P.; Fabricatore, Carlo (2016)
Cognitive training aimed at older adults is introduced and the issues of engagement and adhesion are discussed. Two examples of ‘brain training’ games are analysed, one with a health (non-leisure) focus that is currently being deployed in a clinical trial (Protect Brain Training Study) and the other focussed on leisure that is available on a consumer games console (Big Brain Academy for Wii). Both are based on a set of mini-games which are aimed at training and/or testing reasoning, planning, concentration, identification, maths, visuospatial and memory skills. The game mechanics of the two examples are analysed in detail, summarised and discussed. The paper concludes with an outline of the future research direction.